2013
DOI: 10.1080/09540121.2012.752562
|View full text |Cite
|
Sign up to set email alerts
|

Trends in risk behaviors among female sex workers in south India: Priorities for sustaining the reversal of HIV epidemic

Abstract: HIV epidemic in India is predominantly concentrated in subgroups of population, such as female sex workers (FSWs) and their clients, whose behavior exposes them to a higher risk of acquiring HIV infection. This paper aims to present the changing patterns of socio-demographic characteristics, behaviors, reported sexually transmitted infections (STIs), and associated factors among FSWs over 11 years. Multistage cluster sampling with probability-proportional-to-size (PPS) method was used in the surveys. A sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A study from India assessing risk behaviors among sex workers suggested that illiterate sex workers were 1.6 times more likely to have STI symptoms and be involved in risky sexual behaviors compared to literate sex workers. 23 Another study from Tanzania found condom use was positively associated with increasing education levels. 24 Regarding self-reported reasons for not using condoms, all KP groups indicated high rates to the categories of "I trust the client", "Condoms were not available", and "Under the influence of drugs/alcohol".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from India assessing risk behaviors among sex workers suggested that illiterate sex workers were 1.6 times more likely to have STI symptoms and be involved in risky sexual behaviors compared to literate sex workers. 23 Another study from Tanzania found condom use was positively associated with increasing education levels. 24 Regarding self-reported reasons for not using condoms, all KP groups indicated high rates to the categories of "I trust the client", "Condoms were not available", and "Under the influence of drugs/alcohol".…”
Section: Discussionmentioning
confidence: 99%
“…6,9,17 Studies suggest that condom use among FSWs may differ between consistent partners and shorter-term paying clients. 6,9,23,25,26 In a study from South Africa, FSW avoided condoms with personal sex partners due to the negative symbolism of condoms representing disease, infidelity, and mistrust. 26 Another study assessing partner type and condom use among FSW reported that romance facilitates poor condom use, as condom use was perceived as unattractive.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, living with intimate partners may add to sex workers' debt burdens and economic insecurity and increase the violence in their lives (Reed et al 2010), constraining their capacity to practice condom use with clients. The secret or hidden condition of some women's sex work and the need to prevent intimate partners from discovering it contribute to the importance of separating work and private relations (Charles et al 2013), constraining condom use practice with those intimate partners. At the same time, many sex workers' private partnerships begin through their sex work, and distinguishing these relations from commercial relations takes on more importance as they evolve, also constraining condom use practice (Shaw and Pillai 2012).…”
Section: Structural Relations Of Domestic Settings Instituted In Housmentioning
confidence: 99%
“…4,5 However, as women of reproductive age, FSWs also have reproductive needs, fertility intentions and children. The same behaviors that place FSWs at risk for HIV and STIs can also place them at risk for unwanted pregnancy, but only a small body of literature has considered their reproductive health such as pregnancy histories and contraceptive use.…”
Section: Introductionmentioning
confidence: 99%